2021
DOI: 10.1093/geronb/gbab075
|View full text |Cite
|
Sign up to set email alerts
|

Prodigal Children: Why Older Mothers Favor Their Once-Deviant Adult Children

Abstract: Objectives Past research suggests that adult children who reform their deviant behaviors (i.e., problems with drugs/alcohol or the law) are more likely to become favored by their mothers, yet the reasons underlying this phenomenon are unclear. This study employs a longitudinal, qualitative approach to explore why adult children’s behavioral reforms shape changes in maternal favoritism. Method Analyses are based on qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Similarly, work by Suitor and colleagues showed that mothers sometimes favored reformed deviants over all of their other offspring. Further, a recent qualitative article from the same group (Kincaid et al, 2021) revealed such cases of "prodigal children" occurred only when adult children desisted from their deviant behaviors and showed appreciation for their mothers' support in helping them overcome these problems. However, mothers in the current study did not report such changes in their relationships with any of the offspring from whom they were estranged at T1.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, work by Suitor and colleagues showed that mothers sometimes favored reformed deviants over all of their other offspring. Further, a recent qualitative article from the same group (Kincaid et al, 2021) revealed such cases of "prodigal children" occurred only when adult children desisted from their deviant behaviors and showed appreciation for their mothers' support in helping them overcome these problems. However, mothers in the current study did not report such changes in their relationships with any of the offspring from whom they were estranged at T1.…”
Section: Discussionmentioning
confidence: 99%
“…The Time 1 sample consisted of 566 mothers, which represented 61% of those who were eligible for participation, a rate comparable to that of similar surveys in the 2000s (Wright & Marsden, 2010). (Further details of the design can be found in Kincaid et al, 2022; Suitor & Pillemer, 2006; Suitor et al, 2013 and at https://web.ics.purdue.edu/%7Ejsuitor/within-family-differences-study, where portions of this section have been published previously. )…”
Section: Methodsmentioning
confidence: 99%